Activity limitations and participation restrictions in people with multiple sclerosis: a detailed 10-year perspective. Issue 3 (30th January 2021) - Conradsson, David; Ytterberg, Charlotte; Engelkes, Catharina; Johansson, Sverker; Gottberg, Kristina
Abstract: Aim: To conduct a detailed investigation into changes in activity limitations and participation restrictions over 10 years in people with mild, moderate and severe multiple sclerosis. Methods: This study was a 10-year longitudinal study of 264 people with multiple sclerosis living in Stockholm County, Sweden. Ten-year changes in personal and instrumental activities in daily living were assessed using the Katz Activities in Daily Living Index Extended and participation in social/lifestyle activities using the Frenchay Activities Index. Results: While people with moderate multiple sclerosis, compared to baseline, demonstrated significantly higher proportions of dependency in most activities of personal and instrumental activities in daily living at the 10-year follow-up, the mild group primarily increased their dependency in instrumental activities and the severe group in personal activities. Significantly higher proportions of the moderate group showed restricted participation in domestic and outdoor activities whereas the mild group only showed restrictions in a few domains of participation. A majority of people with severe multiple sclerosis showed restricted participation in all social/lifestyle activities at baseline and the 10-year follow-up. Conclusions: Prominent long-term increases in activity limitations and participation restrictions occurred across the spectrum of disease severity but was most pronounced in those more moderately affected. Implications for rehabilitation: This study provides guidance with regard to specific activities that are prone to deteriorate across 10 years and thereby reflect important targets and outcomes for interventions. Increases in activity limitations and participation restrictions were most pronounced in those moderately affected by multiple sclerosis. Those mildly affected by multiple sclerosis primarily increased their dependency in instrumental activities of daily living while those severely affected increased their dependency in personal activities of daily living.